A novel hypomorphic allele of Spag17 causes primary ciliary dyskinesia phenotypes in mice - Zakia Abdelhamed; Marshall Lukacs; Sandra Cindric; Heymut Omran; Rolf W. Stottmann (The Company of Biologists, 2020)
Primary ciliary dyskinesia (PCD) is a human condition of dysfunctional motile cilia characterized by recurrent lung infection, infertility, organ laterality defects and partially penetrant hydrocephalus. We recovered a mouse mutant from a forward genetic screen that developed many of the hallmark phenotypes of PCD. Whole-exome sequencing identified this primary ciliary dyskinesia only (Pcdo) allele to be a nonsense mutation (c.5236A>T) in the Spag17 coding sequence creating a premature stop codon (K1746*). The Pcdo variant abolished several isoforms of SPAG17 in the Pcdo mutant testis but not in the brain. Our data indicate differential requirements for SPAG17 in different types of motile cilia. SPAG17 is essential for proper development of the sperm flagellum and is required for either development or stability of the C1 microtubule structure within the central pair apparatus of the respiratory motile cilia, but not the brain ependymal cilia. We identified changes in ependymal ciliary beating frequency, but these did not appear to alter lateral ventricle cerebrospinal fluid flow. Aqueductal stenosis resulted in significantly slower and abnormally directed cerebrospinal fluid flow, and we suggest that this is the root cause of the hydrocephalus. The Spag17Pcdo homozygous mutant mice are generally viable to adulthood but have a significantly shortened lifespan, with chronic morbidity. Our data indicate that the c.5236A>T Pcdo variant is a hypomorphic allele of Spag17 that causes phenotypes related to motile, but not primary, cilia. Spag17Pcdo is a useful new model for elucidating the molecular mechanisms underlying central pair PCD pathogenesis in the mouse. This article has an associated First Person interview with the first author of the paper.